PHYSICOCHEMICAL AND NUTRITIONAL CHARACTERIZATION OF SEED OIL FROM Dacryodes edulis (AFRICAN PEAR) - ASANJA JOCK, ALEXANDER; SIMON , NZIKAHYEL; APKAN, SARAH E. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Dacryodes Edulis is a plant with multiple applications ranging from its leaves, bark, flowers, root and fruits. In this study, oil from bush African pear (Dacryodes Edulis) seed was extracted and characterized. The proximate nutritional composition, physicochemical properties and GCMS analysis of the oil was carried out. The acid value, saponification value, peroxide value and iodine value were found to be 7.59 mgKOH/g, 185.1 mgKOH/g, 2.8 mgKOH/g and 3.96 mgKOH/g respectively. The oil yield was 50.6% while moisture content was 29.0%. The ash content, crude protein, fat content, crude fibre and carbohydrate determined were 2%, 11.9%, 19.6%, 25.5% and 12% respectively. The gas chromatography-mass spectrometry (GCMS) conducted on the oil revealed predominantly the presence of 9, 12-octadecadienoic and linoelaidic acids. Compounds like n-hexadecenoic acid and cyclopentane undecanoic acid were in moderate amount. Ethyl ester, oleic acid and pentadecanoic acid were in minor quantities while prop-1-en-2-yltridecyl ester was in trace amount. The result from the investigation revealed that the oil from bush pear has potential of being used as an industrial raw material and as food additives.